Towards equity in development : a report on the status of women in sixteen Commonwealth Caribbean countries - Mondesire, Alicia (Caricom Secretariat GeorgetownGY, 1995)
Analyses the assumptions underlying global and regional development trends, and their relationship to women in the Commonwealth Caribbean. Diagnoses and analyses areas of critical concern and presents strategic goals in the plan of action.